Global talent management by multinational enterprises post‐COVID‐19: The role of enterprise social networking and senior leadership. (3rd January 2022) - Chatterjee, Sheshadri; Chaudhuri, Ranjan; Vrontis, Demetris; Mahto, Raj V.; Kraus, Sascha
Abstract: Multinational enterprises' (MNEs') workforce is made up of people from diverse backgrounds and different locations around the globe. The cross‐border transfer of knowledge, skills, and best practices among MNE employees is important to maintain global standards and competitiveness. In the post‐COVID‐19 period, there is a greater need to exchange knowledge in the changing business environment. The purpose of this study is to examine the issues related to MNEs' global talent management, post‐COVID‐19. The study investigates the use of enterprise social networking applications for better knowledge exchange and tries to understand the moderating role of senior leadership team support in facilitating the usage of enterprise social networks for cross‐border collaboration and talent management. After reviewing the literature and relevant theories, we developed a conceptual model, which is then validated using the SEM technique with 347 respondents from 12 MNEs. The study reveals the importance of using enterprise social networks for cross‐border knowledge exchange in the post‐COVID‐19 period.